Tort law (functions) - Papayannis, Diego M. (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
In this essay, I analyze the functions most frequently attributed to tort law. I claim that implementing interpersonal justice is its only distinctive function. The rest of the functions can be satisfied by other institutions with equal or greater success than tort law. Finally, I try to show that some functions, without being distinctive, are necessary, in the sense that once a system of tort law is in place, they are unfailingly fulfilled.